Assessment of platelet function in patients with stroke using multiple electrode platelet aggregometry: a prospective observational study. Issue 1 (December 2016) - Sabra, Ahmed; Stanford, Sophia; Storton, Sharon; Lawrence, Matthew; D'Silva, Lindsay; Morris, Roger; Evans, Vanessa; Wani, Mushtaq; Potter, John; Evans, Phillip
Abstract Background There is a link between high on-treatment platelet reactivity (HPR) and adverse vascular events in stroke. This study aimed to compare multiple electrode platelet aggregometry (MEA), in healthy subjects and ischaemic stroke patients, and between patients naive to antiplatelet drugs (AP) and those on regular low dose AP. We also aimed to determine prevalence of HPR at baseline and at 3–5 days after loading doses of aspirin. Methods Patients with first ever ischaemic stroke were age and sex-matched to a healthy control group. Three venous blood samples were collected: on admission before any treatment given (baseline); at 24 h and 3–5 days after standard treatment. MEA was determined using a Mutliplate® analyser and agonists tested were arachidonic acid (ASPI), adenosine diphosphate (ADP) and collagen (COL). Results Seventy patients (mean age 73 years [SD 13]; 42 men, 28 women) were age and sex-matched to 72 healthy subjects. Thirty-three patients were on antiplatelet drugs (AP) prior to stroke onset and 37 were AP-naive. MEA results for all agonists were significantly increased in AP-naive patients compared to healthy subjects: ADP 98 ± 31 vs 81 ± 24, p  < 0.005; ASPI 117 ± 31 vs 98 ± 27, p  < 0.005; COL 100 ± 25 vs 82 ± 20, p  < 0.005. For patients on long term AP, 33% (10/30) of patients were considered aspirin-resistant. At 3–5 days following loading doses of aspirin, only 11.1% were aspirin resistant based on an ASPI cut-off value of 40 AU*min. Conclusions Many patients receiving low dose aspirin met the criteria of aspirin resistance but this was much lower at 3–5 days following loading doses of aspirin. Future studies are needed to establish the causes of HPR and potential benefits of individualizing AP treatment based on platelet function testing.